Peningkatan Kesadaran Hukum Masyarakat Indramayu Mengenai Prosedur Perkara di Pengadilan Agama Melalui Sosialisasi Berbasis Pengalaman PKL Mahasiswa IAI Padhaku - Kusyana, Kusyana (Kusuma: Jurnal Pengabdian kepada Masyarakat, 2024)
This 30-day Community Service Program through Field Work Practice (PKL) by IAI Padhaku students in Indramayu aimed to enhance public legal awareness regarding court procedures at the Religious Court. Through socialization based on PKL experience, students directly interacted with the community, identified legal issues faced, and provided comprehensive understanding of the litigation flow and requirements. Activities included outreach, interactive discussions, and distribution of informative materials tailored to the local community's needs. The results of this service demonstrated an increased public understanding of religious court proceedings, which is expected to reduce potential legal problems and improve access to justice. This program also provided valuable experience for students in practically applying legal knowledge and contributing to community empowerment.